Observed Apixaban Anti-Xa Levels in Obese Patients. Issue 11 (November 2022) - Harkness, Weston; Pipitone, Olivia; Joss, Jacqueline; Schiedler, Michael; Shagavah, Santon; Moore, Ryan; Hsing, Jeff
Background: Recent guidelines suggest that, for venous thromboembolism (VTE), standard doses of apixaban are appropriate in patients with body mass index (BMI) >40 kg/m2 or >120 kg. Atrial fibrillation (AF) is excluded from this recommendation. Objective: The goals of our study were to measure and describe anti-Xa levels of patients with a BMI ≥40 kg/m2 and/or a weight ≥120 kg with a clinical indication of AF or VTE who were treated with apixaban, and to determine whether BMI or weight are associated with anti-Xa levels in this population. Methods: We conducted an observational cohort study at a single health care system in Oregon, USA. Patients meeting enrollment criteria were recruited and had peak and trough apixaban anti-Xa levels drawn. Results: Of 55 patients enrolled, 5 (9%) had peak anti-Xa levels below the reference range and 3 (6%) had trough anti-Xa levels below the reference range. BMI did not significantly correlate with peak or trough anti-Xa levels (r = −0.10, p = 0.45 and r = −0.14, p = 0.31). Weight had a moderate, negative correlation with peak anti-Xa levels (r = −0.42, p = 0.002) and a weak, negative correlation with trough anti-Xa levels (r = −0.32, p = 0.02). Conclusions and Relevance: This study provides evidence that anti-Xa levels among obese patients are not substantially different from patients with nomral BMI and weight. This supports recent ISTH guidance for standard dosing of apixaban for VTE patients with BMI >40 kg/m2 or weight >120 kg and provides additional evidence that the standard dosing may also be appropriate in patients with AF.